Peran Pancasila dalam Pembentukan Etika Generasi Muda di Era Modern dan Globalisasi - Amar, Muhamad Syafron (Maliki Interdisciplinary Journal, 2026)
The development of the era of disruption marked by the Industrial Revolution 4.0 to the transformation towards Society 5.0 has had a significant impact on the social and moral life of Indonesia’s young generation. The flow of globalization and the dominance of digital media not only presents opportunities for progress, but also raises various ethical challenges, such as cyberbullying, the spread of hoaxes, hate speech, increasing individualism, and a hedonistic lifestyle that has the potential to weaken social ethics and national identity. This research aims to analyze the ethical challenges faced by the young generation in the modern era and globalization and examine the role of Pancasila in the formation of the ethics of the younger generation as an effort to overcome the moral crisis. The research method used is a qualitative study with a literature review approach to various scientific sources that are relevant to the values of Pancasila, character education, and ethics of the younger generation. The results of the study show that the values of Pancasila have strong relevance as the foundation of social ethics and digital ethics, both in social life and in the digital space. The internalization of Pancasila values through Pancasila education and Civic Education, strengthening character education, and the use of social media as a means of education are considered effective in forming a young generation that is ethical, tolerant, and nationalist. This research emphasizes that the revitalization of Pancasila as an ethical system is an urgent need so that the younger generation is able to face the challenges of globalization without losing moral and national identity in the modern era.